Bartonella rochalimae in Raccoons, Coyotes, and Red Foxes - Jennifer B. Henn; Bruno B. Chomel; Henri-Jean Boulouis; Rickie W. Kasten; William J. Murray; Gila K. Bar-Gal; Roni King; Jean-François Courreau; Gad Baneth (Emerging Infectious Diseases, 2009)
To determine additional reservoirs for Bartonella rochalimae, we examined samples from several wildlife species. We isolated B. rochalimae from 1 red fox near Paris, France, and from 11 raccoons and 2 coyotes from California, USA. Co-infection with B. vinsonii subsp. berkhoffii was documented in 1 of the coyotes.